2020
DOI: 10.1111/1748-5967.12437
|View full text |Cite
|
Sign up to set email alerts
|

An overview of insect innate immunity

Abstract: Due to the exposure of insects to various sources of pathogens during different stages of their life cycle and their vulnerability towards subsequent infections, moreover lack of morality issues, economical breeding and short‐term‐life cycle, insect's immunity has been considered as a high‐potential candidate to study underlying mechanisms of defense responses against all sort of invaders, as well as pandemic diseases. Currently, the world is enduring monumental pressure to meet global food production demands.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 54 publications
0
58
0
Order By: Relevance
“…Toll receptors have been identified and known to recognize evolutionarily conserved bacterial components such as LPS, LP, LPT, and PGN in mammals [ 31 , 63 ]. Moreover, it has been reported that CD14 facilitates LP recognition by toll-like receptors 2 and 1 in humans [ 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Toll receptors have been identified and known to recognize evolutionarily conserved bacterial components such as LPS, LP, LPT, and PGN in mammals [ 31 , 63 ]. Moreover, it has been reported that CD14 facilitates LP recognition by toll-like receptors 2 and 1 in humans [ 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…For multicellular animals, innate immunity is an efficient first line of defense to avoid pathogen invasion and activate different signaling pathways [1]. Invertebrates, such as insects, lack an adaptive immune system and mainly depend on the innate immune system to counter the diverse pathogens that include fungi, bacteria and viruses [2].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, insects have evolved to be very successful organisms, occupying almost every habitat and ecological niche. This is due to a strong innate immune system consisting of a cellular and a humoral component (reviewed by [12][13][14]). The cellular defense is initiated instantly when pathogens are detected and results in the phagocytosis of smaller pathogens or encapsulation of bigger invaders [13,14].…”
Section: Insect Innate Immunitymentioning
confidence: 99%
“…The cellular defense is initiated instantly when pathogens are detected and results in the phagocytosis of smaller pathogens or encapsulation of bigger invaders [13,14]. The humoral defense is a relatively slow response and involves the production of a series of antimicrobial peptides (AMPs), complement proteins, lysozymes, protease inhibitors, reactive oxygen species (ROS), and enzyme cascades leading to the formation of melanin and clotting [12,14].…”
Section: Insect Innate Immunitymentioning
confidence: 99%